Study of Some Chemical, Physical and Microbiological Properties of Five Types of Local Iraqi Date Products and Their Impact on Green Marketing - Jbara, Abdulwahab Abdulrazaq; Saleh, Siril Mahdi; Ahmad Sameer. N. Al-Thabit (Nabatia, 2024)
This study aims to analyze the chemical, physical and microbiological characteristics of five varieties of local Iraqi dates, and the impact of these characteristics on the green marketing possibilities of these varieties of dates, with the aim of raising awareness about their value and enhancing their use in local and international markets. The results showed that the highest average of carbohydrates and sugars was in dates. Bream (59.81), (0.71), while the highest average in proline and protein was in the Khastawi variety (27.47), (2.54). The results also showed that the P-Value was less than 0.05, which indicates the presence of statistically significant differences between the types. Dates differ in their content of (carbohydrates, sugars, proline, and protein). As for the microbiological characteristics, including aerobic and anaerobic bacteria, fermentation, and rotting, the study revealed the presence of microbial contamination in all samples, and the date varieties showed differences in microbial groups, where the Al-Maktoum variety had the largest number. Of the aerobic and anaerobic bacteria (34,000), (2,800), while Barhi has the largest number of yeasts and molds (420), (260).